2015
DOI: 10.1155/2015/478150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increased Water Intake on Urinary DNA Adduct Levels and Mutagenicity in Smokers: A Randomized Study

Abstract: The association between fluid intake and bladder cancer risk remains controversial. Very little is known about to which extent the amount of water intake influences the action of excreting toxics upon the urinary system. This proof of concept trial investigates the effect of water intake on mutagenesis in smokers, a high risk population for bladder cancer. Methods. Monocentric randomized controlled trial. Inclusion Criteria. Male subjects aged 2045–45 y/o, smokers, and small drinkers (24-hour urinary volume <1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Recently, Buendia et al [ 42 ] observed a slight decrease in urinary adducts formation and significantly decreased urinary mutagenicity with increasing water intake in male smoker, which firstly proved urogenous contact hypothesis. So for the purpose of preventing bladder cancer in European and American population, apart from limiting intake volume as mentioned above without changing drinking style, try to drink more non-tap water as well as tea may also help.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, Buendia et al [ 42 ] observed a slight decrease in urinary adducts formation and significantly decreased urinary mutagenicity with increasing water intake in male smoker, which firstly proved urogenous contact hypothesis. So for the purpose of preventing bladder cancer in European and American population, apart from limiting intake volume as mentioned above without changing drinking style, try to drink more non-tap water as well as tea may also help.…”
Section: Discussionmentioning
confidence: 91%
“…It has been observed that the development of cancer in some sensitive tissues, such as the breast, is probably related to hormonal imbalance [ 46 ]. Breast cancer is caused when the DNA in breast cells mutate, disrupting specific functions that control cell growth and division.…”
Section: Types Of Cancer and Their Causesmentioning
confidence: 99%
“…Считается, что потребление достаточного количества жидкости влияет на диурез и, соответственно, на частоту опорожнения мочевого пузыря, что приводит как к уменьшению концентрации канцерогенов в моче, так и к сокращению времени их воздействия на эпителий мочевого пузыря [7]. В рандомизированном исследовании с участием 65 курильщиков увеличение потребления воды в течение 50 дней значительно снижало потенциал мутагенности мочи [8]. Популяционные исследования, посвященные изучению связи объема потребления жидкости и риска развития РМП, показали противоречивые результаты.…”
Section: питание и рак мочевого пузыряunclassified